2021
DOI: 10.3390/plants10040721
|View full text |Cite
|
Sign up to set email alerts
|

Proximate Analyses and Amino Acid Composition of Selected Wild Indigenous Fruits of Southern Africa

Abstract: A literature survey revealed that several wild indigenous Southern African fruits had previously not been evaluated for their proximate and amino acid composition, as well as the total energy value (caloric value). Fourteen species including Carissa macrocarpa, Carpobrotus edulis, Dovyalis caffra, Halleria lucida, Manilkara mochisia, Pappea capensis, Phoenix reclinata, and Syzygium guineense were analyzed in this study. The nutritional values for several species such as C. edulis, H. lucida, P. reclinata, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 65 publications
1
9
0
Order By: Relevance
“…Lys exhibits significant thermal instability even at low temperatures [19]; therefore, some losses may have occurred during the drying and roasting processes and its concentration may be higher in S. madagascariensis fresh fruits. Although in low amounts, nfuma presents all nine essential AA, which is in agreement with the findings of Sibiya et al [42], who found eight essential AA (Trp was not evaluated) in 14 indigenous fruits.…”
Section: Amino Acids and Protein Nutritional Qualitysupporting
confidence: 91%
See 3 more Smart Citations
“…Lys exhibits significant thermal instability even at low temperatures [19]; therefore, some losses may have occurred during the drying and roasting processes and its concentration may be higher in S. madagascariensis fresh fruits. Although in low amounts, nfuma presents all nine essential AA, which is in agreement with the findings of Sibiya et al [42], who found eight essential AA (Trp was not evaluated) in 14 indigenous fruits.…”
Section: Amino Acids and Protein Nutritional Qualitysupporting
confidence: 91%
“…Lys and Met were significantly higher in protein from Chicualacuala flour (16.9 mg/g protein) and Chókwè (15.6 mg/g protein), respectively, and Trp was significantly lower in protein from Marracuene flour (10.3 mg/g protein). Studies on the AA composition of indigenous fruits is scarce in the literature [ 42 ], and no information is available for fruits or products of Strychnos spp. [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From the perspective that wild food plants are increasingly considered a potential source of natural healthy products, it is fundamental to foster biochemical research aimed at documenting their nutritional properties and main bioactive products [8,9]. The phytochemical and nutritional profiles of the species in question can therefore constitute basic knowledge for food pairing with other ingredients to improve nutritional and/or sensory quality and to find innovative cooking methods, allowing key molecules responsible for functional properties to be enhanced.…”
mentioning
confidence: 99%